Call centre workers unite! changing forms of organisation and representation in the Portuguese and British Digital Economy. (1st December 2018) - Isabel Roque
Abstract : In the 21st century the introduction of digital technologies has been accompanied by a rise in precarious, cheap and vulnerable work. Call centres represent a part of the service sector that exemplifies many aspects of technological innovation, being one of the fastest developing forms of digitalised work. This article draws on 30 semi-structured interviews conducted between 2014 and 2017 with former and present Portuguese and British call centre workers, trade union delegates, activists and academics, aiming at analysing the engagement between trade unions and social mobilisation, that is, how workers engage in new forms of organisation in Portuguese and British call centres.